Developing strong and tough cellulose acetate/ZIF67 intelligent active films for shrimp freshness monitoring. (15th February 2023) - Zhang, Yan; Tang, Qun; Huang, Kangqi; Xu, Zongshu; Feng, Shaoxiong; Li, Heping; Zou, Zhiming
Abstract: There is a growing demand for the development of intelligent active packaging films to maintain and monitor the freshness of meat food. Herein, nano Co-based MOF (ZIF67) with ammonia-sensitive and antimicrobial functions was successfully synthesized and then integrated into cellulose acetate (CA) matrix to prepare intelligent active films. The impacts of ZIF67 incorporation on the structure, physical and functional characteristics of CA film were fully investigated. The results demonstrated that the ZIF67 nanofillers were evenly dispersed in CA matrix, resulting in remarkable improvement on tensile strength, toughness, thermal stability, UV barrier, hydrophobicity and water vapor barrier ability of CA film. Furthermore, the prepared CA/ZIF67 films exhibited superb antimicrobial and ammonia-sensitive functions. The CA/ZIF67 intelligent films turned their color from blue at beginning to brown during progressive spoilage of shrimp. These results revealed that the CA/ZIF67 films with excellent antimicrobial and ammonia-sensitive functions could be applied in intelligent active food packaging. Graphical abstract: Unlabelled Image